MENINGKATKAN KEKUATAN OTOT TUNGKAI MELALUI LATIHAN SQUAT - Ika Sartika; Abdul Rasyid (Indonesian Journal Of Physical Activity and Sport Development (IJPASD), 2023)
Squat exercises have a significant effect on increasing strength. Squat exercises will affect the gluteus, gastrocnemius, quadriceps, hamstring, and hip flexor muscles. Basic squat exercise to develop strength in the legs and groin. This research is a quasi-experimental research with a "one groups pre-test-post-test design". This research was conducted with 11 subjects. The instrument used in this study was a leg muscle strength test with a vertical jump test. To analyze the research data using the t-test, namely by comparing the results of the pre-test with the post-test in the experimental group. Based on the results of statistical tests, it was obtained that the t-test value between the pre-test and post-test of squat training on increasing leg muscle strength had a t-count value (t-count 10.946 > t-table 1.79588), and a significant value (p = 0.000 <0.05), because the t-count value is greater than t-table and the significant value is less than α (0.05) there is a significant increase between the pre-test and post-test data